Aminoacyl transfer ribonucleic acid synthetase complex-interacting multifunctional protein 1 induces microglial activation and M1 polarization via the mitogen-activated protein kinase/nuclear factor-kappa B signaling pathway - Oh, Yebin; Jung, Hak-Jun; Hong, Seungwon; Cho, Yerim; Park, Jiyeong; Cho, Daeho; Kim, Tae Sung (Frontiers in Cellular Neuroscience, 2022)
Activation of microglia, which are the primary immune cell of the central nervous system, plays an important role in neuroinflammation associated with several neuronal diseases. Aminoacyl tRNA synthetase (ARS) complex-interacting multifunctional protein 1 (AIMP1), a structural component of the multienzyme ARS complex, is secreted to trigger a pro-inflammatory function and has been associated with several inflammatory diseases. However, the effect of AIMP1 on microglial activation remains unknown. AIMP1 elevated the expression levels of activation-related cell surface markers and pro-inflammatory cytokines in primary and BV-2 microglial cells. In addition to the AIMP1-mediated increase in the expression levels of M1 markers (interleukin (IL)-6, tumor necrosis factor-α, and IL-1β), the expression levels of CD68, an M1 cell surface molecule, were also increased in AIMP-1-treated microglial cells, while those of CD206, an M2 cell surface molecule, were not, indicating that AIMP1 triggers the polarization of microglial cells into the M1 state but not the M2 state. AIMP1 treatment induced the phosphorylation of mitogen-activated protein kinases (MAPKs), while MAPK inhibitors suppressed the AIMP1-induced microglial cell activation. AIMP1 also induced the phosphorylation of the nuclear factor-kappa B (NF-κB) components and nuclear translocation of the NF-κB p65 subunit in microglial cells. Furthermore, c-Jun N-terminal kinase (JNK) and p38 inhibitors markedly suppressed the AIMP1-induced phosphorylation of NF-κB components as well as the nuclear translocation of NF-κB p65 subunit, suggesting the involvement of JNK and p38 as upstream regulators of NF-κB in AIMP1-induced microglial cell activation. The NF- κB inhibitor suppressed the AIMP1-induced M1 polarization of the microglial cells. Taken together, AIMP1 effectively induces M1 microglial activation via the JNK and p38/NF-κB-dependent pathways. These results suggest that AIMP1 released under stress conditions may be a pathological factor that induces neuroinflammation.